Effects of preexistent hypertension on blood pressure and residual renal function after donor nephrectomy. - Tent, H; Sanders, J; Rook, M; Hofker, H; Ploeg, R; Navis, G; van der Heide, J (2012)
BACKGROUND: Living kidney donor selection has become more liberal with acceptation of hypertensive donors. Here, we evaluate short-term and 1- and 5-year renal outcome of living kidney donors with preexistent hypertension. METHODS: We compared outcome of hypertensive donors by gender, age, and body mass index with matched control donors. Hypertension was defined as predonation antihypertensive drug use. All donors had glomerular filtration rate (I-iothalamate) and effective renal plasma flow (I-hippuran) measured 4 months before and 2 months after donation. A subset of donors had serum creatinine measured 1 year after donation or a renal function measurement 5 years after donation. RESULTS: Included were 47 hypertensive donors and 94 control donors (both 53% male; mean age, 57±7 years; and body mass index, 28±4 kg/m). Pre- and early postdonation, systolic blood pressure, and mean arterial pressure were significantly higher in hypertensive donors. Control donors showed a rise in diastolic blood pressure after donation, and thus the predonation difference was lost postdonation. Both at 1 year (29 hypertensive donors, 58 controls) and 5 years after donation (13 hypertensive donors and 26 controls) blood pressure was similar. Renal function was similar at all time points. DISCUSSION: In summary, hypertensive living kidney donors have similar outcome in terms of blood pressure and renal function as control donors, early and 1 and 5 years after donation.